Проблемы разработки: от кило- до нанометров; Научно-технический вестник ОАО "НК "РОСНЕФТЬ"; № 2 (23) - Байков В. А. Виталий Анварович; Газизов Р. К. Рафаил Кавыевич; Латыпов А. Р. Альберт Рифович; Яковлев А. А. Андрей Александрович (2011, 2011)
Заглавие с экрана